Improving leaching efficiency of saline soils using water management techniques - Siyal, Abdul Ghafoor (2011)
Saline soils in arid regions of the world are normally reclaimed by continuous ponding method of the salt leaching. This method wastes large quantities of good quality water that otherwise may be used for irrigation of crops. In water stress region, water use efficient leaching methods are desperately needed. Therefore the salt leaching efficiency of different desalinization methods viz. partial, continuous and intermittent ponding were investigated for medium to fine soil textures i.e. sandy loam, loam, silt loam and clay soil under initially saturated conditions in the laboratory using sand tank model. Experiments of salt leaching from loamy soil with continuous and intermittent ponding under initially unsaturated conditions were also conducted. Computer simulations of salt leaching with continuous and partial ponding scenarios under initially saturated and unsaturated conditions were also carried out with model HYDRUS-2D. Based on literature, a hypothesis that salt leaches quicker when a soil Extrapolation of the partial ponding technique for initially unsaturated soil conditions caused extra 8.1% and 11% water and time savings respectively compared to that used with under initially saturated soil conditions. Computer simulations of salt leaching with HYDRUS-2D revealed that partial ponding method of leaching is a time efficient method of leaching which can save 90.6%, 90.7%, 89.5% and 88.5% time savings compared to continuous leaching for sandy loam, loam, silt loam and clay soil textures respectively. Field experiments results showed that plants are capable of drying root zone, plants extracted water from the entire profile significantly which resulted in approximately uniform moisture content in the soil profile. For both leaching methods salts were leached more from upper layer (0-20 cm) compared with lower soil layer (60-80 cm) because the ECw of water increases as the water percolates down to lower layers which results in decrease in concentration gradient between ECe and ECw and salts were leached more from plots with plants (T3) followed by plots with tillage (T2) and plots without tillage and plants (T1). Tillage expedites the leaching process but when the soil profile is unsaturated it enhances leaching capability even more. Intermittent ponding method of salt leaching found more efficient compared to that of continuous ponding method of leaching, however, intermittent method took 60 days whereas continuous method took 40 days to complete the leaching process.